Checklist of Wild Betta Fish from Sarawak and Captive Breeding Protocols - Mohd Armeen, Zulkanaini (University of Malaysia Sarawak Institutional Repository, 2025)
The genus Betta, (commonly known as fighting fish) includes a diverse group of freshwater fishes with significant ecological and economic roles. However, scientific knowledge of wild Betta species in Sarawak remains limited, with most studies focusing on hybrid species for the ornamental trade. This study aimed to update the checklist of wild Betta in Sarawak and establish captive breeding protocols for selected native species. A total of 72 specimens were collected from seven locations across Sarawak. There were 7 species of wild Betta had been recorded namely, B. ibanorum, B. brownorum, B. lehi, B. midas, B. taeniata, B. akarensis and B. macrostoma. Morphometric comparisons showed that males were generally larger and heavier than females, except in B. ibanorum, where no significant sexual dimorphism was observed. Successful captive breeding was achieved for B. ibanorum, B. macrostoma, B. taeniata and B. brownorum, with documentation of mating behaviour, larval stages and growth performance. These findings provide a foundational reference for future conservation programs and sustainable aquaculture efforts involving Sarawak’s indigenous Betta species.